اللہ تعالیٰ کی طرف غلط منسوب کردہ اسماء کا علمی و تحقیقی جائزہ: An Analytical Study of Incorrectly Ascribed Names to Allah Almighty - Anam Zaidi,; Dr. Hidayat ur Rehman Muhammad Kafil, (Al-Amīr Research Journal for Islamic Studies, 2025)
In our society many names and attributes of Allah Almighty spread which are not authentic. Being a Muslim it is very important for us to know the true and revealed names of Allah Almighty and invented names also, because it is one of the important category of Tawheed and we all know that Tawheed is the first and basic fundamental of Islam and any worship is not acceptable without Tawheed. Through names and attributes of Allah almighty his introduction will be possible and his introduction is nesscesry in the life of Muslim, without knowledge of this it is not possible to worship him correctly, in this article I have tried to collect some invented names so we could aware the false attributes and names of Allah Almighty. Keywords: Importance of Tawheed, Islamic beliefs, Worship in Islam, False names of Allah, Divine attributes in Islam, Allah’s 99 names, Understanding Allah in Islam